Information revolution : 4th PERPUN International Conference, 11-12 August 2015, Avillion Legacy, Melaka - PERPUN International Conference 2015 : Melaka).; Universiti Teknikal Malaysia Melaka. Library (Melaka : Universiti Teknikal Malaysia Melaka, 2015)
At present, the information revolution has swept global world in all aspects of life. Include the libraries in confronting issues and challenges. Library role as information and knowledge repository science to students, academic staff and society has undergone drastic changes in line with the pace of technology. The information revolution has change and have a big impact in world of management and information services.
Includes 12 presentation slide and abstracts.
Disc characteristic: CD-ROM
Description based on PDF title page.
Keywords: Information science -- Congresses; Information organization -- Congresses; Web applications -- Library applications; Information storage and retrieval systems